Targeting JAK-STAT Signalling Alters PsA Synovial Fibroblast Pro-Inflammatory and Metabolic Function - O’Brien, Aisling; Hanlon, Megan Mary; Marzaioli, Viviana; Wade, Siobhan C.; Flynn, Keelin; Fearon, Ursula; Veale, Douglas J. (Frontiers in Immunology, 2021)
Objectives: Psoriatic arthritis (PsA) is a chronic inflammatory disease associated with psoriasis. Janus Kinase inhibitors (JAKi) have emerged as an encouraging class of drugs for the treatment of PsA. Here, we compare the effect of four JAKi on primary PsA synovial fibroblasts (PsAFLS) activation, metabolic function, and invasive and migratory capacity. Methods: Primary PsAFLS were isolated and cultured with JAKi (Peficitinib, Filgotinib, Baracitinib and Upadacitinib) in the presence of Oncostatin M (OSM). Pro-inflammatory cytokines/chemokines were quantified by ELISA and cell migration by wound-repair scratch assays. Invasive capacity was examined using MatrigelTM invasion chambers and MMP multiplex MSD assays. PsAFLS bioenergetics was assessed using the Seahorse XFe Extracellular Flux Analyzer, which simultaneously quantifies two energetic pathways- glycolysis (ECAR) and Oxidative phosphorylation (OCR). In parallel, inflammatory, invasive, and migratory genes were quantified by RT-PCR. Results: OSM-induced secretion of MCP-1 and IL-6 was inhibited by all JAKi with Peficitinib, Baracitinib and Upadacitinib showing the greatest effect. In contrast, JAKi had no significant impact on IL-8 secretion, with an increasing trend observed for IL-8 mRNA expression. PsAFLS cell invasion, migration capacity and MMP1, 3, and 9 were suppressed following JAKi treatment, Peficitinib showing the greatest effect. These functional effects were accompanied by a change in the cellular bioenergetic profile of PsAFLS, where JAKi significantly decreased glycolysis and the ECAR/OCR ratio, resulting in a shift to a more quiescent phenotype, again Peficitinib demonstrating the most pronounced effect. Conclusion: This study demonstrates that JAK/STAT signalling mediates the complex interplay between inflammation and cellular metabolism in PsA pathogenesis. This inhibition shows effective suppression of inflammatory mechanisms that drive pathogenic functions of PsAFLS, further supporting the role of JAKi as a therapeutic target for the treatment of PsA.